Health Education: Junk Food and Its Dangers to Children's Health - Ulfa Nurullita; Trixie Salawati; Wulandari Meikawati; M. Faisal Rofie; Dimas Saputra (JURNAL INOVASI DAN PENGABDIAN MASYARAKAT INDONESIA, 2026)
Background: Elementary school-aged children are highly vulnerable to environmental influences on their dietary behaviors, particularly the frequent consumption of nutrient-poor snacks and fast food. The widespread availability and aggressive marketing of energy-dense, nutrient-poor foods have contributed to unhealthy eating habits, increasing the risk of obesity and other non-communicable diseases. Similar concerns were identified among children attending the At-Tanzil Hicom Learning Center in Shah Alam, Malaysia, many of whom come from socioeconomically disadvantaged families with limited parental supervision and low educational attainment. Objective: This community service program aimed to improve children's knowledge and awareness of healthy eating habits and the health risks associated with fast-food consumption through interactive nutrition education. Method: The program involved 15 children and two teachers. Educational interventions were delivered using interactive counseling supported by visual learning media, including flashcards, educational games, posters, brochures, and the development of a healthy school canteen proposal. Program outcomes were evaluated through direct observation of participants' understanding and engagement during educational activities. Result: Before the intervention, participants demonstrated limited knowledge of basic nutrition and healthy food choices. Following the educational sessions, children showed substantial improvements in their ability to distinguish healthy foods from unhealthy alternatives and to recognize the health risks associated with fast-food consumption. The use of visual aids and game-based learning effectively enhanced participants' comprehension, engagement, and active participation, despite their limited literacy levels. Conclusion: Interactive nutrition education is an effective approach for improving children's knowledge and awareness of healthy eating behaviors. However, sustained behavioral change requires continuous nutrition education, active parental involvement, and supportive school environments, including the implementation of healthy school canteen policies. Keywords: health education, health risks, junk food _________________________________________________________________________ Abstrak Latar belakang: Anak usia sekolah dasar sangat rentan terhadap pengaruh lingkungan, khususnya dalam perilaku makan, termasuk seringnya mengonsumsi camilan rendah nutrisi dan makanan cepat saji. Ketersediaan dan pemasaran makanan padat energi dan miskin nutrisi yang meluas telah berkontribusi pada pola makan yang tidak sehat, peningkatan risiko obesitas, serta penyakit tidak menular. Masalah ini juga terjadi di kalangan anak-anak Indonesia di Pusat Pembelajaran At-Tanzil Hicom di Shah Alam, Kuala Lumpur, yang sebagian besar berasal dari keluarga kurang mampu dengan pengawasan orang tua yang terbatas, dan latar belakang pendidikan yang rendah. Tujuan: Program pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan kesadaran anak-anak tentang pola makan sehat dan risiko Kesehatan dari makanan cepat saji. Metode: Program ini melibatkan 15 anak dan 2 guru. Intervensi meliputi penyuluhan interaktif menggunakan media visual (kartu flash), permainan edukatif, poster, brosur, dan pengembangan proposal kantin sehat. Hasil: Hasil kegiatan menunjukkan bahwa anak-anak awalnya memiliki pengetahuan terbatas tentang nutrisi dasar. Namun, setelah sesi interaktif berulang, kemampuan mereka untuk mengidentifikasi makanan sehat dan mengenali makanan cepat saji meningkat. Metode visual dan berbasis permainan terbukti efektif dalam meningkatkan pemahaman dan keterlibatan meskipun terdapat keterbatasan literasi. Kesimpulan: Pendidikan kesehatan interaktif efektif meningkatkan pengetahuan gizi anak-anak. Perubahan perilaku yang berkelanjutan membutuhkan pendidikan terus-menerus, keterlibatan orang tua, dan lingkungan yang mendukung seperti kantin sekolah yang sehat. Kata kunci: bahaya kesehatan, junk food, pendidikan kesehatan